Reporting Biological Assets on SAK-ETAP Perspective (A Case Study on Dairy Cattle Farming in Dairy Farming in Oro-Oro Ombo Village, Batu City) - Muhammad Irsan Y Hi Wahid; Puji Handayati; Rizky Firmansyah (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2020)
The purpose of this study was to determine how the accounting treatment of biological assets according to the SAK-ETAP perspective regarding recognition, measurement, reporting and disclosure of financial statements. Suggest that you record financial reports according to SAK ETAP standards so that they can be used as decision-making materials for Oro-oro Ombo's dairy farms. reporting of biological assets in accordance with standards and also in accordance with existing facts can be profitable in the dairy farming business in the future. This research is a qualitative research with a case study research type. The subjects of this study were Oro-oro Ombo's dairy farm and the research object was dairy cows. The primary data used in this study are the results of interviews with informants who are directly responsible for managing the cattle farm business. Meanwhile, secondary data is used to support the primary in the form of documents that are related to the object of research. The results showed that the recognition of biological assets in the form of cows in accounting treatment according to cattle breeding is recognized as fixed assets and the measurement of biological assets is measured at fair value or equal to market prices. The reporting carried out by the farm includes a simple report that only shows the amount of income received for a month and also records the expenses incurred by the farm. Disclosure of biological assets on farms in the form of dairy cows contains a policy that does not recognize the classification of assets based on assets based on the productive life of the assets. So that the biological assets on Oro-oro Ombo's dairy farm, starting from recognition, measurement, reporting and disclosure are not in accordance with SAK-ETAP standards.